2015
DOI: 10.1139/cjfr-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of forest legacies following two mountain pine beetle outbreaks in British Columbia, Canada

Abstract: Abstract:The mountain pine beetle, Dendroctonus ponderosae Hopkins (Coleoptera, Curculionidae), a native insect of North America, periodically reaches population sizes that cause serious economic impact to the forest industry in western North America. The most recent outbreak in British Columbia (BC), Canada, which began in the late 1990s, is only now (2015) abating, after causing unprecedented tree mortality in lodgepole pine (Pinus contorta Douglas ex. Loudon) forests. In this paper, we make use of permanent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…Balsom et al (1996) hypothesized that the removal of mature cover would lead to lower moose densities because of lower forage availability and malnutrition. In our study, moose selection for the Pine cover class did not decrease as cover quality declined (in response to canopy die-off after MPB), perhaps because blowdown provided lateral cover and restricted access by hunters and predators, and there was more preferred regenerating browse (Timmermann and McNicol 1988, Rempel et al 1997, Alfaro et al 2015. Salvage logging in central BC removed the Pine cover class, which may be important for moose as a source of cover and forage, and therefore could leave moose more vulnerable by creating large forest clearings.…”
Section: Use Availability and Selectionmentioning
confidence: 60%
See 4 more Smart Citations
“…Balsom et al (1996) hypothesized that the removal of mature cover would lead to lower moose densities because of lower forage availability and malnutrition. In our study, moose selection for the Pine cover class did not decrease as cover quality declined (in response to canopy die-off after MPB), perhaps because blowdown provided lateral cover and restricted access by hunters and predators, and there was more preferred regenerating browse (Timmermann and McNicol 1988, Rempel et al 1997, Alfaro et al 2015. Salvage logging in central BC removed the Pine cover class, which may be important for moose as a source of cover and forage, and therefore could leave moose more vulnerable by creating large forest clearings.…”
Section: Use Availability and Selectionmentioning
confidence: 60%
“…Our results emphasize that female moose utilize forest cover, heterogeneous landscapes, and areas with browse abundance in large clearcut landscapes. Other researchers have shown that following large-scale bark beetle outbreaks, without the intervention of clear-cutting practices, forests maintain heterogeneity in vertical and horizontal structure, diversity of understory species, and high stocking standards (Alfaro et al 2015, Winter et al 2015). Our work also highlights that if clear-cutting of MPB-killed pine stands continues in these study areas, the effective carrying capacity of the landscape for female moose may continually decrease if forest harvesting occurs at a rate that exceeds the regrowth of forestry plantations that produce adequate moose habitat.…”
Section: Management Implicationsmentioning
confidence: 99%
See 3 more Smart Citations